“Okay We’re Doing My Idea”: How Students Enact Epistemic Agency and Power in a Design-Based Engineering Context - Christina L. Baze; María González-Howard; Victor Sampson; Richard Crawford; Xiaofen Hamilton (Education Sciences)
Science and engineering practices are intended to engage students authentically in the work that scientists and engineers do in order to provide opportunities for meaningful engagement in disciplinary work, including design-based learning. Meaningful engagement, particularly for sensemaking purposes, requires a shift in who is leading the classroom community’s intellectual work, from the teacher to the students. When students are positioned with the intellectual responsibility of producing and evaluating ideas, there is potential for them to act with epistemic agency. Enacting epistemic agency involves socially negotiated framing and power dynamics. The purpose of this study is to determine the ways in which gendered power dynamics influence the negotiation of epistemic agency in a design-based learning context. Using a qualitative case study methodology, student negotiations of epistemic and positional framing from a mixed-gender group were observed. Transcripts from their discourse during two design challenges were mapped, and focal group interviews were holistically analyzed to understand students’ perceptions and navigation of epistemic and positional framings in a design-based learning context and to understand how power dynamics influence these negotiations. Students understood the epistemic goals of the design challenges to involve designing solutions to real-world problems. During the first challenge, the group distributed positions of epistemic authority among the members. However, the group experienced a change in composition, resulting in changed power dynamics and epistemic oppression. These findings have implications regarding the critical impact that classroom culture and interactional practices might have on students’ epistemic agency, especially considering their multiple identity markers.